Quantum Correlation Dynamics in Controlled Two-Coupled-Qubit Systems - Iulia Ghiu; Roberto Grimaudo; Tatiana Mihaescu; Aurelian Isar; Antonino Messina (Entropy, 2020)
We study and compare the time evolutions of concurrence and quantum discord in a driven system of two interacting qubits prepared in a generic Werner state. The corresponding quantum dynamics is exactly treated and manifests the appearance and disappearance of entanglement. Our analytical treatment transparently unveils the physical reasons for the occurrence of such a phenomenon, relating it to the dynamical invariance of the X structure of the initial state. The quantum correlations which asymptotically emerge in the system are investigated in detail in terms of the time evolution of the fidelity of the initial Werner state.